Methodological Characteristics of the Teaching of Professional Reasoning in Kinesiology: Qualitative Study - Araya-Ávila, Jonathan (2025)
Background. The initial training of healthcare professionals has exhibited persistent declared dysfunction since the Alma Ata declaration, which exposed the difficulties of conditioned reasoning due to mimetic assimilation in problem-solving. Objective. To understand the methodological characteristics of the processes used by teachers in teaching professional reasoning (PR) to kinesiology students. Methodology. A qualitative interpretive study was conducted using a purposive sampling method, through semi structured interviews (SSI) with 9 expert teachers (ET) in PR from accredited universities. The interviews were recorded on the Microsoft TEAMS® platform. Data were collected during 2020-2023 in 5 selected Chilean Kinesiology schools based on curricular evidence and ranking. Results. The emerging themes identified in the interviews with teachers were transcribed and coded using the Atlas.ti® software. It was found that the characteristics of case study analysis in different applications stood out as the predominant methodology in teaching PR, while the most recurrent assessment instrument was the Rubric. Conclusions. There is a wide range of strategies used by ETs to teach PR. These strategies consist of both traditional methodologies and more student-centered active resources, with theoretical and practical aspects characterized by the formative moment, the selected model, and the imprecise taxonomic articulation of strategies and assessment instruments. This highlights the need for a greater integration of factors for the learning of PR.